Delayed Reconstruction with Full-Thickness Skin Grafts Following Defect Size Reduction in Head and Neck Nonmelanoma Skin Cancer - Sezgin, Baha; Kaya, Isa; Turhal, Goksel; Apaydin, Fazil (Facial Plastic Surgery, 2020)
Different treatment modalities have been applied for nonmelanoma skin cancers (NMSCs) of the head and neck area. One of the most important points after surgical treatment is the selection of appropriate reconstruction methods. The aim of this study is to investigate the efficacy and feasibility of the use of both defect size reduction with sutures and secondary healing with delayed reconstruction with full-thickness skin grafts in NMSC patients. In total, 18 (42.8%) male and 24 (57.2%) female patients with NMSC were operated. Defect size was measured both after excision and just before repair, and the approximate defect area was calculated with ImageJ software. Reconstruction was performed after 14 days in all patients in the second session, using free skin grafts. There were 18 (42.8%) male and 24 (57.2%) female patients. The mean age was 70.5 (45–82) years. The mean follow-up period was 40.3 (16–68) months. The mean defect area measured after excision was 8.44 ± 1.91 cm2. After 14 days of delay, the mean defect area was 5.51 ± 1.28 cm2 (34.8% reduction) (p < 0.05). Defect-reduction methods applied during the first session, together with proper interval prior to placement of graft, have been shown to be beneficial and acceptable methods, providing an advantage in reconstruction with free skin graft.
Keywords: nonmelanoma skin cancers; defect size; defect reduction; full-thickness skin grafts; ImageJ software